METODOLOGI RISET BAGI PERKEMBANGAN TEORI AKUNTANSI - Michell Suharli (Media Riset Akuntansi, Auditing & Informasi, 2007)
This paper explains development of accounting theory in the context accounting as a science. As a science, theory should developed by empirical research. In first portion we try to explain about relationship between research and theory. We explore how accounting can be a science. It should involve discussion and research in positive accounting theory. Then we descript classification of research, method, efficient market hypothesis and capital asset pricing models as resull of empirical research, and relationshrP between research, theory and practice in accounting. In conclusion we can understand that research methodology has important rule in development of accounting theoryKey Words: research methodology! theorizing, science, efficient market hypothesis, capital assets pricing model